Dampak Otonomi Fiskal, Pertumbuhan Ekonomi, dan Keterbukaan Daerah Terhadap Ketimpangan Wilayah di Sumatera - Fajri, Muhammad; Delis, Arman; Amzar, Yohanes Vyn (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176), 2017)
The main research to identify the impact of fiscal autonomy,economic growth,openness access into inequality amongprovinces in Sumatera. For analyze the effect of the degree of fiscal autonomy, economic growth, and openness access to the inequality in Sumatera period2009-2013 withRandom Effect Method. The results explain fiscal autonomy are categorized low. Economic growthin Sumatera during the study period was also low. Openness access in Sumatera can be said is still not open to trade. Inequality in the Sumatera still quite high. The effect of fiscal autonomy to inequality is negative and significant. Economic growth to inequality is negative and significant, while the openness access is positive and not significant to inequality. Expected in Sumatera provincial governments to used maximum local revenue. Economic growth must observe and control the level of inequality. There should be a boost to the regions to be more active in trade traffic in Sumatera or National.
Keywords: fiscal autonomy, economic growth; opennessaccess; inequality; regression panel data analysis